Enhancing Reading Fluency in English Among Grade 6 Learners Through Project 4P’s - Nones, Jeff Benedict V. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Reading fluency—the ability to read with accuracy, automaticity, and prosody—is essential for comprehension. This study employed a quasi-experimental one-group pretest-posttest design to enhance the English reading fluency of 31 Grade 6 learners at Luna Central School through Project 4P’s during the 2023-2024 school year. The Philippine Informal Reading Inventory (PHIL-IRI) Assessment Tool was used to determine learners' initial fluency levels and measure improvements after the intervention. Their pretest and post-test scores were analyzed using the mean and compared using a dependent t-test. Results revealed that prior to the intervention, learners' reading fluency was categorized as Frustration, indicating significant difficulty in reading. Following the implementation of Project 4P’s, their fluency improved to Independent, demonstrating substantial progress in reading proficiency. Statistical analysis showed a significant difference between pretest and post-test scores, confirming the effectiveness of Project 4P’s in improving literacy skills. These findings underscore the value of structured reading interventions in fostering fluency and comprehension. Consequently, the researcher recommends adopting Project 4P’s as a viable strategy for improving English reading fluency among Grade 6 students, with potential applicability in similar educational settings.